Preparing 'middle actors' to deliver zero-carbon building transitions. Issue 1 (21st September 2020) - Simpson, Kate; Janda, Kathryn B.; Owen, Alice
The urgent transition to a zero-carbon economy requires building professionals to be supportive of, and prepared for, delivering zero-carbon buildings. Building professionals are important 'middle actors' who can either enable or inhibit such societal transitions. This paper explores building professionals' perspectives on delivering zero-carbon buildings, leading to a practical synthesis of knowledge and skill requirements and training pathways. It draws on the middle-out perspective (MOP) and secondary analysis of three UK case studies. The MOP suggests that middle actors in a system are not perfectly responsive to policy push or market pull. Instead, they exert their own agency and capacity downstream to customers and clients, sideways to other middle actors and, occasionally, upstream to policy-makers. The data comprise: interviews and a small survey with building professionals on energy efficiency and refurbishment; the observation of a specific commercial office building design and development and a workshop to identify zero-carbon knowledge and skill needs of middle actors. Building professionals addressed in this paper include vocational trades, engineers, designers, project managers and 'clerks of works' (site-based quality technicians). Although formal training pathways for these roles differ, each can develop expertise 'sideways' interacting between professions. Practice relevance: Collaboration between academia, vocational training and industry could support sideways initiatives to better enable delivery of zero-carbon buildings. Policy-makers and regulators need to create routes to capture, listen to and use the perspectives of building professionals. At present, these actors have very little upstream influence. Middle-actor groups in construction undertake different activities, but share training routes, knowledge support systems and professional networks. These routes, systems and networks would allow actors to facilitate change from the 'middle-out' in a way complementary to top-down change driven by policy and bottom-up changes led by citizens. Training routes can include formal, on-the-job (informal) or e-learning. Prioritising on-the-job knowledge-sharing could promote upskilling. Roles such as a clerk of works could assist in overseeing construction processes. Vocational professionals are the priority group of middle actors to build capacity, knowledge and influence.